Copper(II)-catalyzed aerobic oxidation of hydrazides to azo intermediates and their Diels–Alder versus ene trapping - Chaiyaveij, Duangduan; Whiting, Andrew (Arkivoc, 2024)
The oxidation of diethyl 1,2-hydrazinedicarboxylate using a catalytic Cu(II)-oxazoline system occurs at RT in air, resulting in azo generation, which can then be trapped in situ via hetero-Diels-Alder (HDA) and competitive ene-reactions, with chemoselectivity being both temperature and solvent dependent. The procedure was extended to other azo systems and mechanism studies are reported.
EPrint Processing Status: Full text deposited in DRO
Keywords: Biophysical Sciences Institute (BSI)